How Students Make Model and Promote Productive Struggle in Solving Mathematical Problems - Melani, Rini; Herman, Tatang; Prabawanto, Sufyani; Samosir, Christina Monika; Mefiana, Syifa Ananda (STKIP Singkawang, 2024)
Making mathematical models involves translating real-life situations into mathematical expressions. This research, conducted in three Bandung schools with 93 students, focuses on iconic and symbolic mathematical models. Findings reveal that students' abilities using these models are below the expected minimum, with symbolic models being more dominant. The score difference may be influenced by the teacher's role, students' experiences, individual abilities, and specific contexts favoring visual understanding. Students face challenges in making mathematical models, including a lack of comprehensive understanding, difficulty identifying variables, creating context-free models, and struggling with relevant visualizations. Additionally, they encounter issues using formulas and interpreting mathematical results when answering questions. In the validation stage, adjusting temporary results to real situations poses challenges. Internal factors contributing to difficulties include a lack of interest, critical limitations, and low self-confidence. External factors like a limited practical experience in making models also play a role. A holistic solution addressing both internal and external factors is essential for students to overcome challenges and enhance their ability to create mathematical models from real-world contexts. The recommended role of the productive struggle learning approach is crucial in assisting students in achieving the expected milestones.